Morph Functional Changes of Ferments in the Neutrophiliac of Peripheral Blood in the Case of Virus Hepatitis B at Children (Eurasian Medical Research Periodical, 2023)
The activity of SDG, LDG, G-6-FDG and £-GFDG at ill children has been studied. The change of ferments activity in depending of VHB course heaviness has been investigated. Steady and deep lowering of dehydrogenizes activity was marked at 6 patients (6,8%) with fulminant form of VHB. It was concluded that t VHB the aerobic way of carbohydrate transformation (SDG) is sharply disordered, β-glycerol phosphate (β-GFD) and peptone phosphate (G-β-FDG) bypasses are suffered, as well as glycolysis (LDG) is activated. It is evidence of acute changes in energy phenomena, leading to the gathering of lactate and metabolic acidosis. Steady lowering of dehydro genesis is prognostically unfavorable indicator of VHB course.